Les sages-femmes traditionnelles de Papantla : changements et persistances dans l’offre de soin en santé maternelle au Mexique - Amandine Debruyker (Centre de Recherches sur les Mondes Américains, 2015)
For the past thirty years, the medical institutions try to establish themselves in Mexico in the region of Papantla (Veracruz). Health centers have been settled and aim at answering the need for primary health care of local populations. Despite this institutional presence, turning to traditional midwives to deal with issues of maternal and child health is still common today, even though the vast majority of births are handled by medical professionals. This article suggests bringing to light some areas of reflection regarding the role and the status of the traditional midwives of Papantla in this context of diffusion of the modern biomedical practices. The ethnographic description of the rites and the practices which accompany the pregnancy, the birth and the puerperal care in this region allows us to make more explicit the complexity of the practices of the traditional midwives. These traditional midwives are characterized by a desire to adapt and conform themselves to the elements of modernity. At the same time, they want to stay loyal to the traditional ways and they remain attached to a Meso-American conception of the existence.